Assessment of concentrations of interleukin-25 in bronchial asthma – preliminary studies - Czarny-Działak, Małgorzata A.; Słuszniak, Anna (Medical Studies/Studia Medyczne, 2016)
Introduction : Studies have demonstrated an important role of cytokines in the development of asthma, in particular the balance between them disturbed in favour of pro-inflammatory cytokines. Interleukin-25 (IL-25) belongs to the family of cytokines from IL-17. Its role in the pathogenesis of allergic diseases of the respiratory tract is not entirely clear. The study took into account the fact that the role can be very important due to the dual mechanism of action as an anti-inflammatory and inflammatory stimulant. Aim of the research : To assess whether the concentration of IL-25 depends on the the severity of the course of asthma. Material and methods: The study involved 80 people: 20 volunteers and 60 patients with asthma – 20 people with mild persistent asthma, 20 with moderate, and with 20 severe. All patients were maintained on a course of asthma control. From each patient, blood was drawn to assess IL-25 ELISA test; all patients also had spirometry performed (in the framework of visits to the clinic). Results : In none of the cases of the people from the examined group there was an increased level of IL-25. However, some subjects (17) had higher levels of this interleukin than other people – among these were four volunteers and 13 patients with asthma. Conclusions : In the future patients should be checked during exacerbations of asthma and have the response time tried to be extended to maximum so that we can measure lower concentrations, which within a standard procedure could has not been varied (found below the lowest standard).